The Impact of Uncertainty on Earned Value Analysis - Ur Rahman, Ubaid (2011)
ABSTRACT This dissertation was carried out to study the impact of uncertainty factors on Earned Value Management (EVM). There are many uncertainty factors associated with Earned Value Analysis (EVA), one of the main factors being predicting the Budget for each month. The primary objective of this dissertation was to study the impact of uncertainty on EVA by carrying out EVA without using Monte Carlo Simulation (MCS) and by carrying out EVA using MCS. The results obtained from both the analysis are compared and checked if MCS helps to reduce the uncertainty associated with EVA. The result of this research pointed out that MCS does reduce the uncertainty associated with EVA by adjusting the values of Budget at completion (BAC). Crystal Ball software was used to perform MCS in order to obtain the mean value used to carry out EVA. Comparisons made thus show that the uncertainty associated with BAC are reduced after every month as the project progresses by taking into account the Actual Cost spent after each month.